2012
DOI: 10.1007/s10457-011-9472-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation among and within provenances of Adansonia digitata L. (Baobab) in seed germination and seedling growth from selected natural populations in Malawi

Abstract: Baobab (Adansonia digitata L) trees have a wide variety of subsistence and economic values across sub-Saharan Africa. Knowledge of the genetic variation within and between the species is essential for management and designing domestication, improvement and conservation strategies.Fifty-nine half-sib families were evaluated in the nursery to determine the genetic variation and control within and between the populations from four silvicultural zones. Seed germination and seven seedling growth parameters were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The seeds were pretreated through nicking to allow water penetration. Mzuzu University lies in silvicultural zone M and falls at an altitude of 1270m above sea level with mean annual temperature range of 13.5°C to 24°C and mean annual rainfall of 1150mm12.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The seeds were pretreated through nicking to allow water penetration. Mzuzu University lies in silvicultural zone M and falls at an altitude of 1270m above sea level with mean annual temperature range of 13.5°C to 24°C and mean annual rainfall of 1150mm12.…”
Section: Methodsmentioning
confidence: 99%
“…The use of baobab tree parts has been reported to vary from place to place3. In Malawi, a study revealed that people in Chikhwawa (56.3%) and Karonga (46.4%) utilize baobab root for medicinal purposes12. In southern Malawi, an infusion of baobab root has for a long time been used to treat sore throats13.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge on the existing genetic variation within and between populations is essential for the species management, its domestication and the application of breeding and conservation strategies , Munthali et al 2012. The molecular markers and the common garden tests are two powerful tools applied for the characterization of genetic variation in forest tree populations.…”
Section: Introductionmentioning
confidence: 99%
“…However, natural reproduction and regeneration cycles of baobab are threatened due to damage caused by domestic animals and seedlings clearance for other land use (Assogbadjo et al 2009). Furthermore, the increased harvesting of fruits from wild or semidomesticated individuals for commercial purposes is suspected of potentially reducing seeds available for the spontaneous generation of new plants (Munthali et al 2012). Domestication and cultivation programmes are thus urgently needed to preserve genetic diversity, maintain multiple specimens and promote the cultivation of varieties suitable for commercial cultivation (Assogbadjo et al 2011;Cuni Sanchez et al 2011).…”
Section: Introductionmentioning
confidence: 99%